PENGARUH ROLE PLAY BELANJA TERHADAP HASIL BELAJAR PENGENALAN KESETARAAN MATA UANG SISWA KELAS II SEKOLAH DASAR - Aldila Putri Monalisa; Muhammad Juliansyah Putra; Nora Surmilasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Introduction to currency equivalence is one of the materials that has many applications in everyday life. This study aims to determine whether role-playing shopping games have an effect on mathematics learning outcomes in the subject of currency equivalence at SD Negeri 13 Tungkal Ilir. The method used in this study is a quasi-experimental research method, with a posttest-only control group design. The population in this study is all students at SD Negeri 13 Tungkal Ilir. The sample in this study consisted of class II A as the experimental class with 28 students and class II B as the control class with 27 students. The data collection techniques used were tests and documentation. The data analysis techniques used were data normality tests, data homogeneity tests, and hypothesis tests. From the results of the hypothesis test calculations, a sig. (2-tailed) of 0.000 < 0.05. Therefore, it can be concluded that Ho is rejected and Ha is accepted, meaning that there is an effect of the shopping role-play game on mathematics learning outcomes in the currency equivalence introduction material for Class II at SD Negeri 13 Tungkal Ilir